2014
DOI: 10.5600/mmrr.004.03.a02
|View full text |Cite
|
Sign up to set email alerts
|

Affordable Care Act Risk Adjustment: Overview, Context, and Challenges

Abstract: Abstract:Beginning in 2014, individuals and small businesses will be able to purchase private health insurance through competitive marketplaces. The Affordable Care Act (ACA) provides for a program of risk adjustment in the individual and small group markets in 2014 as Marketplaces are implemented and new market reforms take effect. The purpose of risk adjustment is to lessen or eliminate the influence of risk selection on the premiums that plans charge and the incentive for plans to avoid sicker enrollees.Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Regarding outcomes, no generally valid conclusions on the effect of ACO participation could be drawn. Some of the studies reported partially positive effects for patient experience [ 51 , 52 ] and mortality [ 53 ], whereas others did not find any effects [ 49 , 50 , 54 , 55 ]. Nejati et al [ 22 ] evaluated the impact of ACOs in cancer care and reported mixed results but did find some improvements in process quality due to decreased utilization of low-value services within the Medicare Pioneer ACO.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding outcomes, no generally valid conclusions on the effect of ACO participation could be drawn. Some of the studies reported partially positive effects for patient experience [ 51 , 52 ] and mortality [ 53 ], whereas others did not find any effects [ 49 , 50 , 54 , 55 ]. Nejati et al [ 22 ] evaluated the impact of ACOs in cancer care and reported mixed results but did find some improvements in process quality due to decreased utilization of low-value services within the Medicare Pioneer ACO.…”
Section: Resultsmentioning
confidence: 99%
“…In 2014, the US Department of Health and Human Services (HHS) introduced a further revised HCC system for use in redistributing funds among the competing health plans in the new Health Insurance Marketplace (originally called an Exchange) set up in each US state (Kautter et al, 2014a and2014b). That formula started with 264 HCCs and, after applying principles for simplification that drop discretionary, vague and common low-cost HCCs, ends up with 127 HHS-HCCs in the final, preferred model.…”
Section: The Us Centers For Medicare and Medicaid Services (Cms) Hierarchical Condition Category (Hcc) Modelsmentioning
confidence: 99%
“…Risk equalization (RE) models are widely used—Belgium, Germany, Israel, the Netherlands, Switzerland, and the U.S. health care exchanges—for calculating risk‐adjusted payments to health insurers in order to compensate them for predictable differences in individuals' health care expenses (Ash, Porell, Gruenberg, Sawitz, & Beiser, ; Kautter, Pope, & Keenan, ; van de Ven, van de Beck, van de Voorde, Wasem, & Zmora, ). In the presence of premium regulation, as is the case in all of the aforementioned countries, the goal of RE is to mitigate financial incentives for risk selection and thereby achieve a level playing field for health insurers.…”
Section: Introductionmentioning
confidence: 99%